2002
DOI: 10.1007/s00213-002-1079-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of cocaine-seeking behavior by repeated nicotine exposure in rats

Abstract: Rationale-Drugs with addictive liability have a high probability of co-abuse in many addicts. For example, cocaine users are several times more likely to smoke cigarettes than non-cocaine users, and smoking increases during cocaine use. Previous work has provided evidence that nicotine and cocaine have interactive neurochemical effects, particularly with regard to dopamine (DA) transmission.Objectives-The present study examined the impact of nicotine treatment on the reinforcement efficacy of self-administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 48 publications
6
70
2
1
Order By: Relevance
“…For example, nicotine has been shown to increase DA levels in the nucleus accumbens (Di Chiara, 2000) in a manner that is additive or synergistic with the effects of psychomotor stimulants (e.g., Gerasimov et al, 2000). These findings are consistent with studies documenting the involvement of dopaminergic activity in maintaining intravenous self-administration of nicotine itself (Di Chiara, 2000) and with nicotine's ability to dose-dependently increase or decrease intravenous cocaine self-administration behavior (e.g., Bechtholt and Mark, 2002). Together, these results suggest that nicotinic mechanisms can influence the behavioral and neurochemical effects of psychomotor stimulant drugs and vice versa.…”
Section: Introductionsupporting
confidence: 72%
“…For example, nicotine has been shown to increase DA levels in the nucleus accumbens (Di Chiara, 2000) in a manner that is additive or synergistic with the effects of psychomotor stimulants (e.g., Gerasimov et al, 2000). These findings are consistent with studies documenting the involvement of dopaminergic activity in maintaining intravenous self-administration of nicotine itself (Di Chiara, 2000) and with nicotine's ability to dose-dependently increase or decrease intravenous cocaine self-administration behavior (e.g., Bechtholt and Mark, 2002). Together, these results suggest that nicotinic mechanisms can influence the behavioral and neurochemical effects of psychomotor stimulant drugs and vice versa.…”
Section: Introductionsupporting
confidence: 72%
“…Moreover, it is interesting to note that in humans mecamylamine has been found to effectively reduce drug cue-induced cocaine craving (Reid et al, 1999). Together with the fact that there is an interaction between cigarette smoking and abuse of psychoactive drugs such as cocaine (Bechtholt and Mark, 2002;Horger et al, 1992;Kouri et al, 2001;Pich et al, 1997;Reid et al, 1998), it is suggested that mecamylamine may become a potentially effective anti-craving agent for relapse prevention for not only tobacco smoking but also cocaine and likely other psychostimulant use.…”
Section: Discussionmentioning
confidence: 99%
“…Como uma estratégia bem-sucedida para o tratamento da dependência de psicoestimulantes, deve-se incluir o tratamento para dependência de nicotina, pois, por causa do papel proeminente dos receptores nicotínicos nos circuitos de recompensa de drogas 30 , o tratamento sinérgico das duas dependências (crack e tabaco) nesses pacientes aumentaria as chances de evitar uma recaída para uso do crack. Portanto, sugere-se que, para a eficácia do tratamento para dependência de crack, o usuário também deve ser motivado para a abstinência do tabaco.…”
Section: Conclusõesunclassified